(untitled) (Swiss Medical Weekly, 2017)
INTRODUCTION Health professionals were found to have an elevated burnout risk compared to the general population. Some studies also reported more emotional exhaustion – a component of burnout – for health professionals with informal caregiving responsibilities for children (double-duty child caregivers) or adults (double-duty adult caregivers) or a combination of both (triple-duty caregivers) compared to health professionals without informal caregiving roles (formal caregivers). However, the potential mediating effect of the work-privacy conflict in this relationship as well as differences between occupational groups have not yet been studied in healthcare settings. AIM To assess the impact of informal caregiving on burnout risk among health professionals and whether this relationship is mediated by work-privacy conflict or differs between occupational groups. METHODS Data were collected through an employee survey in six hospitals from German-speaking Switzerland in 2015/2016. Mediation analyses were performed using linear mixed models with fixed effects for caregiving situation and work-privacy conflict as well as random effects for hospitals. RESULTS Triple-duty caregivers were found to have a significantly higher burnout risk compared to formal caregivers only. Work-privacy conflict did not mediate this relationship, except among the “other health professionals” group. CONCLUSION Additional and large-scale studies focusing on the combination of formal and informal caregiving roles are needed to better understand its effect on burnout among healthcare professionals and to evaluate the role of work-privacy conflict.